2012
DOI: 10.1021/la302395x
|View full text |Cite
|
Sign up to set email alerts
|

One-Step-Process Composite Colloidal Monolayers and Further Processing Aiming at Porous Membranes

Abstract: Composite materials consisting of a monolayer of polystyrene spheres (diameters of 430 and 520 nm) and porous silica, filling in the interstices, have been fabricated and characterized. The proposed growth method introduces some novelties as far as the fabrication of this kind of monolayers is concerned, as it probes the compatibility of coassembly (in which a silica precursor, tetraethyl orthosilicate (TEOS), is added to the base colloid) with confined growth in a wedge-shaped cell, while profiting from the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…With acidic-functionalised core-shell particles, the acidic chains can both catalyze the sol gel reaction and bridge between the particles and the inorganic matrix further stabilizing the 3D system. It has been reported that the presence of TEOS during casting results in less cracking between ordered domains for rigid spheres [16,11].…”
Section: Crosslinked Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…With acidic-functionalised core-shell particles, the acidic chains can both catalyze the sol gel reaction and bridge between the particles and the inorganic matrix further stabilizing the 3D system. It has been reported that the presence of TEOS during casting results in less cracking between ordered domains for rigid spheres [16,11].…”
Section: Crosslinked Samplesmentioning
confidence: 99%
“…Solvent properties, especially volatility, have been shown to affect the degree of self ordering of rigid Nps, i.e. alcoholic solvents increase the quality of crystals in some cases [16]; drying speed (i.e. the drying temperature) of the film was also found to influence the quality of the opal, especially when water is used as casting medium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 The spheres used were made of polystyrene and purchased from Thermo Scientific (polydispersity around 3%). A particle diameter of 870 nm was tested for fabricating the crystals which, in turn, were verified suitable for templating shape-memory structures.…”
Section: Fabrication Of the Templatesmentioning
confidence: 99%
“…Crystalline, colloidal monolayers have been shown to be highly useful for nanolithography [14], structural color painting [5], or as templates for fabrication of porous materials [68]. Common assembly methods to prepare these structures include drop casting, spin coating [911], evaporation [11] on solid substrates, or self-assembly at air/liquid interfaces with subsequent transfer [1, 1219].…”
Section: Introductionmentioning
confidence: 99%